Pneumocystis jiroveci Internal Transcribed Spacer Types in Patients Colonized by the Fungus and in Patients with Pneumocystosis from the Same French Geographic Region - Nevez, Gilles (American Society for Microbiology, 2003)
Pneumocystis jiroveci (human-derived Pneumocystis) infections can display a broad spectrum of clinical presentations, of which pulmonary colonization with the fungus may represent an important part, occurring frequently in patients with various underlying diseases and presenting alternative diagnoses of acute pneumocystosis (Pneumocystis carinii pneumonia [PCP]). There are few data concerning the P. jiroveci genotypes involved in pulmonary colonization, whereas several genotypes responsible for PCP in immunocompromised patients have been described. In this study, P. jiroveci genotypes have retrospectively been investigated and compared in 6 colonized patients and in 11 patients with PCP who were in the same hospital. Seventeen archival bronchoalveolar lavage samples were genotyped at internal-transcribed spacer 1 (ITS1) and ITS2 of the nuclear rRNA operon. Fourteen different genotypes were identified, of which 1 was found only in colonized patients, 10 were found only in patients with PCP, and 3 were found in both patient populations. Mixed infections were diagnosed in 2 of the 6 colonized patients and in 6 of the 11 patients with PCP. The results show that similar genotypes can be responsible for PCP as well as pulmonary colonization. There is a high diversity of genotypes in colonized patients and in patients with PCP. Mixed infections may occur in these two patient populations. These shared features of P. jiroveci ITS genotypes in colonized patients and patients with PCP suggest that human populations infected by P. jiroveci, whatever the clinical manifestation, may play a role as a common reservoir for the fungus.